Se me perdieron las llaves, or Back to the Phenomenon of Guilt in Philosophy of Law Again - O. V. Stovba; Yu. V. Mytsa (Теоретическая и прикладная юриспруденция)
The article is dedicated to the consideration of the phenomenon of guilt in the sphere of legal philosophy. The reasoning of the similar issue is fulfilled both synchronically and diachronically. In the synchronic field of research authors consider the specificity of guilt in the sphere of private law (civil law, commercial law) as such as in the region of public law (criminal law, administrative law). In the context of the diachronic research of the phenomenon of guilt authors turn themselves to the origin of the legal thought — legislation and legal philosophy of Ancient Greece (first of all, pre-Socratic philosophy of law — Parmenides, Heraclitus etc.) and Ancient Rome. The result of the diachronic analyses is the following conclusion. The guilt in its legal-philosophical aspect presents itself originally as the transformed category of the causality. During the contemporary development of the legal thought the latter is substituted by the interpretation of the guilt as the psychological relation of the person, who has committed the legal deed towards its socially dangerous consequences. The similar conclusion is grounded partly on the comparative examination of the obligations, which derivate from contract and from the infliction of the harm (contractual obligation and delict obligation). In the similar case the guilt as the causal relation is existed between the deliberate or negligent action from oneside and the harm, which is derivated from the similar action — from the other. In this situation the category of delict (the break of the norms and rules) is interpreted as the secondary in historical relation and taking place later than phenomenon of causing the harm. In its turn, the synchronic analyze of the phenomenon of guilt leads authors to the hypotheses, that the form of guilt (criminal intent or criminal negligence) is a criterion, which gives us possibility to distinguish the fields of private law and public law. It`s worth to underline that sphere of gross negligence is the border line (so-called mixed zone) between the public and the private law. As the special case authors underline such institute of the civil law as the responsibility without guilt, when the fact of the committing deed (or even the possession of the certain estate) as such creates the ground of the legal responsibility of the person. Finally authors come to conclusion that the real foundation of the legal responsibility is guilt as the fact of involving in the occurrence, i. e. that concrete situation, “case” which is an ontological ground to turn to the law.